2000
DOI: 10.1016/s0378-1097(00)00241-x
|View full text |Cite
|
Sign up to set email alerts
|

Candida glabrata displays pseudohyphal growth

Abstract: The ability to undergo morphological change has been reported as an advantageous trait in fungal pathogenesis. Here we demonstrate that Candida glabrata ATCC2001, like diploid Saccharomyces cerevisiae strains, forms elongated chains of pseudohyphal cells on solid nitrogen starvation media (SLAD). Constrictions were apparent between adjoining cells; no parallel-sided hyphae were seen and pseudohyphae invaded the agar. When SLAD was supplemented with ammonium sulfate both C. glabrata and diploid S. cerevisiae st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 24 publications
1
55
0
Order By: Relevance
“…On agar, colonies grown for 5 days at 25 u C contained approximately the same number of cells, and were visually of similar size, suggesting similar rates of cell multiplication. IWr colonies contained lower concentrations, primarily as a result of a significant proportion of pseudohyphal growth (Lachke et al, 2002;Csank & Haynes, 2000). In liquid culture at 25 u C, the generation times for DB, LB and Wh cells were 1.7, 1.8 and 1.9 h, respectively.…”
Section: Characterization Of the Cell Preparations Used In Animal Modmentioning
confidence: 99%
“…On agar, colonies grown for 5 days at 25 u C contained approximately the same number of cells, and were visually of similar size, suggesting similar rates of cell multiplication. IWr colonies contained lower concentrations, primarily as a result of a significant proportion of pseudohyphal growth (Lachke et al, 2002;Csank & Haynes, 2000). In liquid culture at 25 u C, the generation times for DB, LB and Wh cells were 1.7, 1.8 and 1.9 h, respectively.…”
Section: Characterization Of the Cell Preparations Used In Animal Modmentioning
confidence: 99%
“…glabrata is known to switch to pseudohyphal growth when starved of nitrogen (Csank & Haynes, 2000), but the fungus does not form hyphae during host invasion (Lachke et al, 2002) and only budding growth has been observed in animal tissues (Fidel et al, 1999). In this study, highly FLresistant C. glabrata mutants formed a higher number of budding yeasts and also larger aggregates than the parental control when cultured in FCS, indicating that this attribute may be associated with high FL resistance.…”
Section: Induction Of Yeast Bud Formation and Co-aggregationmentioning
confidence: 99%
“…In both nonpathogenic (Saccharomyces cerevisiae) and pathogenic (Candida albicans, Candida glabrata, and Cryptococcus neoformans) fungi, the ability to switch between the yeast and filamentous form is dependent on environmental conditions. All of these organisms switch from the yeast to the filamentous form when starved for nitrogen (Gimeno et al 1992;Wickes et al 1996;Csank and Haynes 2000;Biswas and Morschhauser 2005). In S. cerevisiae, nitrogen starvation induces pseudohyphal growth in diploid cells (Gimeno et al 1992) and enhances invasive growth in haploid cells cultured on synthetic minimal medium (H. Chen and G. Fink, unpubl.).…”
mentioning
confidence: 99%